Is celiac disease misdiagnosed in children with functional constipation? - Akman, Sezin; Şahaloğlu, Özlem; Dalkan, Ceyhun; Bahçeciler, Nerin Nadir; Arıkan, Çiğdem (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Functional constipation is one of the common problems in childhood, and it comprises approximately 5% of the pediatric outpatient clinical applications. On the other hand, celiac disease (CD) is an immune enteropathy with the prevalence between 1/150 and 1/200. In addition to the classical symptoms of the disease such as diarrhea and weight loss, the incidence of atypical symptoms is increasing. This study aims to determine the prevalence of CD in patients with chronic constipation. Materials and Methods: The study was conducted between 2010 and 2012 and included 1046 children (range, 2-18 y; median, 11.4 y) diagnosed with chronic constipation according to the Rome III criteria. Serum immunoglobulin A, tissue transglutaminase, and/or anti-endomysial antibodies were examined. The patients with serological positive results were subjected to upper gastrointestinal system endoscopy and duodenal biopsy to confirm the diagnosis of CD. Results: Blood tests were positive in 36 patients (3.25%). One of the patients had Hashimoto’s thyroiditis, and 4 patients had short stature. Endoscopic findings included nodularity in bulbus and duodenal mucosa (n=16), scalloping fold (n=13), and normal mucosa (n=5). Histopathologic findings revealed that 10 patients had total villous atrophy, 24 patients had subtotal and partial villous atrophy, and 34 patients had intraepithelial lymphocyte infiltration. All patients followed a gluten-free diet, resulting in a resolution of symptoms. Conclusion: In the present study, a CD ratio of 1:28 was diagnosed in chronically constipated children. The use of screening tests for CD should be considered in children with conventional treatment-resistant constipation. Cite this article as: Akman S, Şahaloğlu O, Dalkan C, Bahçeciler NN, Arıkan C. Is celiac disease misdiagnosed in children with functional constipation? Turk J Gastroenterol 2018; 29: 210-4.